The spread of private tutoring in English in developing societies: exploring students' perceptions. Issue 6 (2nd November 2018) - Hamid, M. Obaidul; Khan, Asaduzzaman; Islam, M. Monjurul
ABSTRACT: Although research on private tutoring has gained visibility in recent years, private tutoring in English (PT-E) has not received notable attention. This paper examines students' perceptions of PT-E in Bangladesh in terms of its necessity and helpfulness, peer pressure in PT-E participation and ethicality of PT-E practice and government intervention. Our analysis of survey data ( N = 572) leads to characterising PT-E and explaining the reasons for its popularity. As a popular learning space beyond formal schooling, PT-E is available in various forms and quality catering to the purchasing power of different social groups. We argue that students may resort to PT-E not because of its proven effectiveness but because of their declining faith in school English teaching. The paper contributes to our understanding of the complex interactions between the curricular (school) and non-curricular (PT-E) settings and family socioeconomic resources in the teaching of English as a globally desired language.